Environmental education for survival: the use of radio among nomads - I Allen (Environmental Association of Southern Africa, 1987)
A Unesco/UNEP project using radio as a medium of environmental education among nomads is described and evaluated. The project, conducted among the Rendille of northern Kenya, aimed inter alia at creating awareness of environmental problems, specifically desertification, fostering positive attitudes towards conservation of resources and sensitizing decision-makers about the need for an integrated, comprehensive resource management policy